Diagnostic Criteria for Major Depressive Disorder in Cancer Patients: A Review. (January 2013) - Guan, Ng Chong; Sulaiman, Ahmad Hatim; Zainal, Nor Zuraida; Boks, Marco P. M.; de Wit, Niek J.
Objectives: The lack of universal criteria makes diagnosing clinical depression in cancer patients a challenging task. We therefore review the current state of evidence regarding such diagnostic criteria for major depressive disorder in cancer patients. Methods: We conducted a literature search for studies which compare two or more sets of diagnostic criteria for depression in cancer patients. The results were extracted and summarized. Results: Three original studies were included in this review. One study supported the use of substitutive (Endicott) criteria. Another study showed the potential of an increased threshold approach and one had no conclusive findings. Conclusion: There was no standard reference test and precise definition of alternative criteria in these studies. There are no recognized diagnostic criteria for depression in cancer patients despite an apparent need for such criteria.